2019
DOI: 10.3389/fimmu.2019.00840
|View full text |Cite
|
Sign up to set email alerts
|

Th2-TRMs Maintain Life-Long Allergic Memory in Experimental Asthma in Mice

Abstract: Allergic asthma is a chronic inflammatory remitting-relapsing disease affecting the airways. Long-lived allergen-specific memory CD4 + T helper 2 (Th2) cells in mice persist in lungs for more than 2 years after the induction of experimental allergic asthma (EAA). To further understand lung Th2 memory cells, we tracked CD4 + T cells in spleen and lungs from healthy mice, through the initiation of acute EAA, recovery (remission), and allergen-induced disease relapse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Allergen-specific immunotherapy aims to provide sustained inhibition of the disease symptoms (35). Given that T cell memory is long-lasting in the OVA-induced allergic respiratory model (36) and that allergen-specific immunotherapy usually require many weeks or years of treatment (37,38) we then next investigated whether our short-term (three-dose) treatment provides a long-lasting effect. For this, after the treatment, the mice were rested for 60 days and then challenged twice with i.n.…”
Section: Treatment With Liposomal Formulation Is Long-lasting Not Rementioning
confidence: 99%
“…Allergen-specific immunotherapy aims to provide sustained inhibition of the disease symptoms (35). Given that T cell memory is long-lasting in the OVA-induced allergic respiratory model (36) and that allergen-specific immunotherapy usually require many weeks or years of treatment (37,38) we then next investigated whether our short-term (three-dose) treatment provides a long-lasting effect. For this, after the treatment, the mice were rested for 60 days and then challenged twice with i.n.…”
Section: Treatment With Liposomal Formulation Is Long-lasting Not Rementioning
confidence: 99%
“…It has been shown that sustained allergic inflammation in the lower airway may require an abundant presence of readily primed memory T cells in peripheral blood that can respond to allergens [35]. CD4+ memory T cells were shown to be involved in recurrent episodes of inflammation in both murine models of BA and BA patients [36,37]. We hypothesized that memory T cells in BA patients display distinctive phenotypes that can sustain chronic inflammation in the lung; and that the expression of certain chemokine receptors on T cells is associated with disease severity and worsening of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 up-regulates chemokine receptors such as CCR4 and CXCR3 that improve migration into the lung, as well as programs related to tissue intention ( 64 ). A recently published paper further reports that these T H 2-T RM cells highly express CD44 and ST2, and can reside in lung tissue and maintain their memory towards allergen for the whole life of a mouse ( 65 ). Once re-exposed to allergen, T H 2-T RM cells robustly proliferate near airways, produce type 2 cytokines, enhance eosinophil activation, and promote peribronchial inflammation.…”
Section: Lung T Rm Cells In Pathologic Immune Respmentioning
confidence: 99%